38.3k views
2 votes
If function / is defined by f(x) = x2 - 2x + 6

and function g is defined by g(x) = 3x - 4,
what is f(g(3))?​

User Vintana
by
4.7k points

1 Answer

4 votes

Answer:

21

Explanation:

Start with the inside first.

The inside is g(3).

g(3) can be found by using function, g.

g(x)=3x-4 so g(3)=3(3)-4=9-4=5.

So now we have that:

f(g(3))

f(5)

We can find f(5) by replacing x in the expression x^2-2x+6 with 5:

(5)^2-2(5)+6

25-10+6

15+6

21

This means f(g(3))=f(5)=21

User PanNik
by
5.3k points